Bad Aboriginal Art : Tradition, Media, and Technological Horizons - Michaels, Eric (Book collections on Project MUSE., 1994)
This is the account of the authors period of residence and work with the Walpiri Aborigines of western Central Australia, where he studied the impact of television on these remote communities. Sharp, exact, and unrelentingly honest, this volume records with an extraordinary combination of distance and immersion the intervention of technology into a remote Aboriginal community and that communitys forays into broadcasting.